DESIGN OF STREAMING EDUCATION CONTENT ON ANDROID BASED MOBILE DEVICE FOR LONG LIFE E-LEARNING - Wahyul Amien Syafei (Jurnal Sistem Informasi, 2013)
This paper presents design of education content streaming applications on Android based mobile devices. It is kind of a learning media that utilizes Internet data services and mobile telecommunications device. The test results prove that the developed system can provide a visual and interactive learning media spontaneously over time (long life learning) and is not limited by space and time. The main component of the education system (task and teaching materials) has also been successfully applied.